Taxonomic revision of African water beetles in the genus Ochthebius Leach (1815), subgenus Aulacochthebius Kuwert (1887) (Coleoptera: Hydraenidae) - Perkins, Philip D. (Zootaxa, 2023)
The African species of the water beetle genus Ochthebius Leach (1815), subgenus Aulacochthebius Kuwert (1887) are revised. Nine new species are described, based on the examination and databasing of 5,911 specimens from 101 localities. Male genitalia are illustrated, and high resolution habitus images of the holotypes and specimens of previously described species are provided. Distribution maps are provided for the sixteen species now known from Africa and Madagascar, including specimens from Angola, Benin, Botswana, Burkina Faso, Chad, Ethiopia, Gambia, Ghana, Kenya, Lesotho, Mali, Morocco, Namibia, Nigeria, Senegal, South Africa, Uganda, Zimbabwe, and Madagascar. New species of O. (Aulacochthebius) are: O. (A.) copiosus n. sp.; O. (A.) flagellissimus n. sp.; O. (A.) latissimus n. sp.; O. (A.) mpumalangicus n. sp.; O. (A.) multilineatus n. sp.; O. (A.) nigeriensis n. sp.; O. (A.) persetosus n. sp.; O. (A.) scutatus n. sp.; and O. (A.) solitarius n. sp. The morphology of O. (A.) exaratus Mulsant, including the aedeagal morphology, is presented, and consequently O. (A.) strangulatus Régimbart is removed from synonymy with O. (A.) exaratus Mulsant.